Uma análise dos projetos políticos pedagógicos dos cursos de Licenciatura em Educação do Campo no Estado do Paraná - Costa, Gelson Kruk da (2013)
This study aims to investigate and analyze the Pedagogical Political Projects (PPPs) formulated with view to implementation of Degree Courses in Rural Education in the State of Paraná, highlighting its characteristics and peculiarities. Thus, the central issue revolves around the analysis of these projects, ensuring that they fulfill the criteria proposed in the formulation of policies of higher education for the people of the countryside, that is, initial training for educators of the field according to the discussion accumulated in the rural social movements, respecting the principles and process developed in this perspective. Therefore, this research considered the PPPs of the four Higher Education Institutions of the State of Parana - EIS, who offered or offer courses. Also in the process the Federal and State Universities, in case the State University of West of Paraná - UNIOESTE State University and the Center - West of Paraná - UNICENTRO the Federal Technological University of Paraná - UTFPR and the Federal University of South Border - UFFS, whose offer of Degree Courses in Rural Education, is realized through public announcements or as a permanent course in the case of UFFS. Universities that offer the course in a non- permanent elaborate projects and raise funds for the Support Programme in Higher Education Degree in Rural Education - PROCAMPO. The analysis of the PPP sought to identify the courses, subjects involved, justifications to offer, goals and curriculum organization, tangential to the political conceptions and pedagogical methodologies. The dissertation is structured into three central chapters of discussion, a discussion that goes permeating the emergence of the bourgeois state, the genesis of social policy, social and political context of the Brazilian countryside, the Field Education in Social Movements forged, PROCAMPO the program, through the PPPs for each HEI to the final debate of an educational policy proposals in political Pedagogical Projects courses. In the final considerations resumed the discussion with the appropriate conclusions emphasizing that public policy proposals have been built by the people of the country, through their organizations and class struggle. The bourgeois state in this context is strained by social movements to legally claim basic rights such as education. The degree courses in Education Field expressing the result as a public policy of this tension.